Dating past colonization events to project future species distributions. Issue 4 (20th January 2019) - Singer, Alexander; Bradter, Ute; Fabritius, Henna; Snäll, Tord
Abstract: Knowledge on the colonization process is important to understand and project future species distributions. The classic method to quantify colonization rates is time‐consuming, as it requires recording infrequent colonization events during extensive, repeated surveys. We present the novel "dating‐based approach" that requires one complete survey of species occurrence and estimates of subpopulation ages to back‐date colonization events. These data allow statistical reconstruction of a virtual, repeated survey to estimate colonization rates in response to environmental covariates or connectivity. With only 30% of survey effort, the dating‐based approach provided similar estimates of rate and distance of dispersal of a metapopulation of the epiphytic moss Neckera pennata as the classic approach relying on long‐term surveys. Projections of the number of colonization events during the next 100 years differed by only 2.3% (95%‐credible interval: [−1.9%; 7.1%]) between methods. The dating‐based approach is applicable across spatial scales and promises enhanced species distribution models with urgently needed quantitative dispersal information.